For the joy set before us: Augustine and self-denying love - Schlabach, Gerald W. (University of Notre Dame Press, 2001)
The problem of self-denial -- The structure of Augustinian caritas -- The grammar of Augustinian continence -- Augustinian continence as a response to the gospel imperative -- The judgment of Augustinian continence -- Sustaining self-denial